Effect of Adding Carrageenan Processing Solid Waste from Eucheuma cottonii to Art Paper Manufacture from Water Hyacinth - Almira Paramitha; Eko Nurcahya Dewi; Retno Ayu Kurniasih (Universitas Gadjah Mada, 2023)
The carrageenan industry produces solid waste E. cottonii of 65% to 70%, so it had the potential to be used as a paper material. The aimed of this study was to analyze the effect of the concentration of E. cottonii waste which was added in the production of art paper from water hyacinth stems on the quality of the paper. The experimental design used was Complete Randomized Design with 1 factor, namely the difference of Eucheuma cottonii waste concentration (0%, 10%, 15%, and 20% (w/w)). The results showed that the addition of carrageenan processing from E. cottonii with difference concentration gave significantly different (p<0.05) on the value of grammage, tensile strength, tear resistance, density, and lightness of the paper. The best concentration of Eucheuma cottonii was 15% because it had the highest tear resistance value (p<0.05) and higher of lightness than the concentration of 0% and 10% (p<0.05). Paper with waste E. cottonii 15% had a grammage 148.93 g/m2; tensile resistance 1.28 kN/m; tear resistance 2497.37 mN; density 1.52 g/cm3; and lightness L* 80.19. The results of microstructure observations using Scanning Electron Microscopy (SEM) were the paper with E. cottonii waste 15% seen less free space (tighter) than other papers. Based on the grammage and tensile resistance value, paper with E. cottonii waste 10% according to Indonesian National Standard 8218:2015 regarding paper and cardboard for food packaging requirements.